2016
DOI: 10.3390/ncrna2020005
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs as Prognostic and Predictive Biomarkers in Patients with Colorectal Cancer

Abstract: MiRNAs are suggested as promising cancer biomarkers. They are stable and extractable from a variety of clinical tissue specimens (fresh frozen or formalin fixed paraffin embedded tissue) and a variety of body fluids (e.g., blood, urine, saliva). However, there are several challenges that need to be solved, considering their potential as biomarkers in cancer, such as lack of consistency between biomarker panels in independent studies due to lack of standardized sample handling and processing, use of inconsisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…These alterations are specific for each malignancy, including various BC subtypes [ 4 , 5 , 7 , 9 , 15 18 ]. Thereby, circulating miRNAs are potential biomarkers in the case of numerous diseases [ 19 ], such as BC [ 15 , 20 22 ]. The studies undertaken to prove the causative effect of miRNA first perform a general profiling of clinical samples, then are followed by controlled experiments [ 22 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…These alterations are specific for each malignancy, including various BC subtypes [ 4 , 5 , 7 , 9 , 15 18 ]. Thereby, circulating miRNAs are potential biomarkers in the case of numerous diseases [ 19 ], such as BC [ 15 , 20 22 ]. The studies undertaken to prove the causative effect of miRNA first perform a general profiling of clinical samples, then are followed by controlled experiments [ 22 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It reported that miRNAs can be secreted by different cells and have been discovered in the bloodstream and bodily fluids [ 54–58 ]. Circulating miRNAs have the potential to be utilized as novel biomarkers for the early diagnosis, treatment and prognosis of several diseases, such as cancer [ 59 ], cardiovascular diseases [ 60 , 61 ], obesity [ 62 ], and diabetes mellitus [ 63 ]. Recent studies demonstrated that serum miRNA levels were markedly up-regulated in patients with osteoporotic fractures and could impact osteogenic differentiation [ 56 ].…”
Section: Circulating Mirnas In Osteoporosis and Bone Fracturementioning
confidence: 99%
“…Certain ncRNAs were found to regulate p53-dependent gene control (21,22). Th ese include microRNAs such as miR-660 and miR-486, which are p53-dependent, and long non-coding RNAs (lncRNAs) such as TUG1 (taurine upregulated gene 1), the p53/TUG1/polycomb repressive complex-2 (PRC2)/homeodomain-containing protein (HOXB7) interaction as targets for the diagnosis and treatment of non-small cell lung carcinoma (NSCLC), miR-34, LincRNA-p21, p53 induced non-coding transcript (Pint) and p21-associated ncRNA DNA damage-activated (PANDA) (24-30) ( Table 1).…”
Section: P53-regulated Mirnasmentioning
confidence: 99%